1992
DOI: 10.1002/cne.903220407
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐immunoreactive terminals synapse on primate spinothalamic tract cells

Abstract: Gamma-aminobutyric acid (GABA) is a putative inhibitory neurotransmitter in the vertebrate nervous system. Several lines of evidence suggest that GABA plays an important role in the processing and modulation of sensory input in the spinal cord dorsal horn. In the present study, the relationship between GABA-immunoreactive (GABA-IR) terminals and spinothalamic tract (STT) cells in the monkey lumbar cord was investigated. Physiologically characterized STT cells, one located in lamina V and two located in lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…One explanation could be that activation of PKG produces a functional change in GABA and glycine receptors on the HT and superficial WDR ST T cells that is different from that on the deep WDR ST T neurons. GABA and glycine receptors have been demonstrated to be distributed in the most layers of the spinal dorsal horn and an inhibitory effect was always seen in deep and superficial WDR ST T cells, as well as HT cells, when these receptors were activated (Willcockson et al, 1984;Carlton et al, 1992;Mitchell et al, 1993;Bohlhalter et al, 1994;Lin et al, 1994Lin et al, , 1996a. Current information, however, fails to provide direct evidence that PKG produces differential effects on I A A receptors in different layers of dorsal horn.…”
Section: Discussionmentioning
confidence: 94%
“…One explanation could be that activation of PKG produces a functional change in GABA and glycine receptors on the HT and superficial WDR ST T cells that is different from that on the deep WDR ST T neurons. GABA and glycine receptors have been demonstrated to be distributed in the most layers of the spinal dorsal horn and an inhibitory effect was always seen in deep and superficial WDR ST T cells, as well as HT cells, when these receptors were activated (Willcockson et al, 1984;Carlton et al, 1992;Mitchell et al, 1993;Bohlhalter et al, 1994;Lin et al, 1994Lin et al, , 1996a. Current information, however, fails to provide direct evidence that PKG produces differential effects on I A A receptors in different layers of dorsal horn.…”
Section: Discussionmentioning
confidence: 94%
“…The terminal density ranged from 30% on the soma to 54% on the distal dendrites (80-120 pm from soma). A low terminal density on lamina I STT cells has been noted in studies in cat and monkey (Ruda et al, 1984;Westlund et al, 1990aWestlund et al, , 1991Westlund et al, , 1992Carlton et al, 1992). Westlund et al (1990aWestlund et al ( , 1991 reported that terminal density on the soma and proximal dendrites of a primate lamina I STT cell was 44% compared with 79% for lamina V STT cells.…”
Section: Organization Of Synapses On Stt Cellsmentioning
confidence: 90%
“…This pattern of more excitatory contacts on the dendrites than on cell bodies is typical of most cells (Peters et al, 1991). However, in dorsal column and in the chief sensory and spinal trigeminal nuclei, there is a preponderance of asymmetrical, glutaminergic contacts onto the somata of projection cells from those nuclei (Maxwell et al, 1991(Maxwell et al, , 1992(Maxwell et al, , 1995Carlton et al, 1992;Westlund et al, 1992). It has been asserted that this may be a characteristic of ''projection neurons'' of the somatosensory system (Maxwell et al, 1995).…”
Section: Ultrastructure Of Incertal Neuronsmentioning
confidence: 96%
“…These data suggest that GABA is the primary neurotransmitter within the ZI (Araki et al, 1984;Ficalora and Mize, 1989;Kim et al, 1992;Donahoe et al, 1996). Most studies have demonstrated that GABAergic synapses throughout the central nervous system have symmetrical junctions (McLaughlin et al, 1975;Ribak et al, 1976Ribak et al, , 1979Oertel et al, 1981;Montero and Singer, 1984;Mize, 1988;Rinvik and Ottersen, 1988;Sotelo et al, 1986;Há mori and Taká cs, 1989; Há mori et al Border and Mihailoff, 1990;Olivier and Beckus, 1991;Peters et al, 1991;Maxwell et al, 1991Maxwell et al, , 1995Mize et al, 1991Mize et al, , 1994Carlton et al, 1992;Asanuma, 1994;Bevan et al, 1995). This characteristic has been used as a definition for inhibitory synapses (Peters et al, 1991).…”
Section: Chemistry Of the Zona Incertamentioning
confidence: 99%